INTEGRAL PRODUCTION OF FRUITS - Keserović, Zoran; Gvozdenović, Dušan; Magazin, Nenad; Vračević, Biserka (Economics of Agriculture, 2007)
The importance of introducing Integral concept in fruitgrowing is been revised in this paper.Considering the importance of fruits in Serbias export, it is very important to start introducing Integral concept of fruits production because internation market will sooner or later impose barriers in front of our fruits growers regarding helth safety and fruits quality. Principles of introducing Integral concept of fruits production are given, which if respected, in many regions of our country would anable establishment of production in accordance with this concept. It is suggested to bring certain legislativ measurs and especialy the book of regulations of Integral production of fruits.